Lithium-ion battery cell and electric device
Patent Information
- Application Number
- CN202611175839.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-30
AI Technical Summary
对于标称尺寸为21700且容量约5Ah的电芯,卷芯外径接近壳体内径,造成卷芯的外圈收尾结构可利用的径向空间有限
本发明在卷芯外圈收尾区域设置收尾胶带和金属收尾层,并定义径向余量Gr、处理后胶带厚度t1、收尾预紧系数Kp和金属收尾空间系数Km,以使收尾结构与壳体内径、卷芯外径以及变化值建立起可测的耦合关系,以提高电芯的质量。
Smart Images

Figure CN123018077A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, specifically to a lithium-ion battery and an electrical device. Background Technology
[0002] All-tab cylindrical lithium-ion cells typically consist of a positive electrode, a separator, and a negative electrode wound into a core, with the axial ends of the positive and negative electrodes flattened or pressed to shorten the electron current collection path. For a cell with a nominal size of 21700 and a capacity of approximately 5Ah, the outer diameter of the core is close to the inner diameter of the casing, resulting in limited radial space available for the outer ring finishing structure of the core.
[0003] Therefore, when designing the structure of a full-tab cylindrical lithium-ion cell, the length and thickness of the tape covering the outer ring of the core should be considered, and a measurable coupling relationship should be established between the tail structure and the inner diameter of the casing, the outer diameter of the core, and the variation value, in order to improve the quality of the cell.
[0004] It should be noted that the information disclosed in the background section above is only used to enhance the understanding of the background of the present invention, and therefore may include information that does not constitute prior art known to those skilled in the art. Summary of the Invention
[0005] To provide a basic understanding of some aspects of the disclosed embodiments, a brief summary is given below. This summary is not intended as a general commentary, nor is it intended to identify key / important components or describe the scope of these embodiments, but rather as a prelude to the detailed description that follows.
[0006] Existing technologies for treating the outer peripheral wall of the core generally include: 1. Ordinary termination tape is mainly used to provide adhesive positioning. If the ordinary termination tape is too thin, the coverage is too short, or the adhesive retention is insufficient, the core is prone to outer ring loosening, axial movement, or end curling after falling and vibration. Simply increasing the tape thickness or coverage length will compress the remaining amount inside the shell, increase the resistance to entering the shell, and cause local compression.
[0007] 2. Setting a metal end layer such as copper foil on the outermost ring of the negative electrode can form an outer ring support and provide a circumferential heat diffusion path using a relatively thin metal layer. However, if the length, thickness and tape coverage of the metal layer do not match the radial margin, it is easy to form a local thick layer area. When the metal end is exposed or the insulation clearance is insufficient, it may also approach the shell, the edge of the active material layer or other conductive components after a drop, vibration or thermal shock.
[0008] 3. Black finishing tape can improve color recognition and thermal diffusion through carbon black, graphite, or other fillers. However, excessive carbon filler content may form a continuous conductive network and reduce volume resistivity; conversely, insufficient filler content makes effective thermal diffusion difficult. Tapes containing liquid-absorbing and expanding particles, thermally expanding microspheres, or elastic microporous structures can compensate for micro-gaps in the outer ring after liquid injection, formation, or heat treatment. However, insufficient expansion cannot maintain pre-tension, while excessive expansion will cause localized pressure on the outer ring of the core.
[0009] This invention addresses the problem of limited solutions in existing technologies by providing a lithium-ion battery cell and related electrical equipment. It solves the problem of poor cell quality caused by a mismatch between the gap between the core and the casing and the finishing structure on the outer periphery of the core. The solution involves complex coordination through techniques such as improving the relationships between the components of the core to ensure specific relationships between them.
[0010] In some embodiments, a lithium-ion battery cell includes a housing and a core coaxially arranged, the core being disposed within the housing; the core is formed by sequentially stacking and winding a positive electrode sheet, a separator, and a negative electrode sheet. The core also includes a finishing layer on at least part of the outer peripheral wall, with a radial allowance Gr between the outer wall of the finishing layer and the inner wall of the shell, the inner diameter of the shell being Di, the maximum outer diameter of the core in the region where the finishing layer is located being Dj, and Gr=(Di-Dj) / 2; The finishing layer includes a metal finishing layer and a finishing tape. The metal finishing layer is in close contact with the outer wall of the core, and the finishing tape covers at least one end of the metal finishing layer. The length of the finishing tape along the winding direction is Lt, and the thickness before covering is t0. The thickness of the finishing tape after being immersed in a 25°C reference electrolyte for 24 hours, then heat-treated at 80°C for 30 minutes, and cooled to 25°C is t1. The thickness of the metal finishing layer is tm, and the length covered along the winding direction is Lm. The units of Lt, t0, t1, Lm, and tm are all mm. It satisfies: Kp=[Lt / (π×Dj)]×(t1 / Gr), and 0.25≤Kp≤1.30; Km=(Lm / Lt)×[(t1+tm) / Gr], and 0.20≤Km≤1.40.
[0011] In some embodiments, the finishing tape includes a substrate layer and an adhesive layer adhered to the substrate layer, wherein carbonaceous filler is dispersed on the substrate layer and / or the adhesive layer; the substrate layer is adhered to the metal finishing layer; the carbonaceous filler accounts for 2wt% to 20wt% of the mass percentage of the finishing tape; and the thickness-direction volume resistivity of the finishing tape at 25°C is 1.0 × 10⁻⁶. 4Ω·cm-1.0×10 10 Ω·cm, in-plane thermal conductivity is 0.30W / (m·K)-3.00W / (m·K).
[0012] In some embodiments, the substrate layer is made of one or more combinations of polyimide, polyethylene terephthalate, polypropylene, polyethylene, aramid paper, and polyamide-imide; the adhesive layer is made of one or more combinations of acrylate pressure-sensitive adhesive, silicone rubber pressure-sensitive adhesive, polyurethane adhesive, and epoxy modified adhesive; and the carbonaceous filler is made of one or more combinations of carbon black, conductive carbon black, graphite, graphene, carbon nanotubes, carbon fiber, and acetylene black.
[0013] In some embodiments, the finishing tape further includes an expanding adhesive layer and an insulating layer, wherein the expanding adhesive layer and the insulating layer sequentially cover the adhesive layer; the expanding adhesive layer includes an acrylic pressure-sensitive adhesive matrix, and one or more combinations of liquid-absorbing and expanding polymer particles, thermally expanding particles, porous elastomer particles and foamed polymer particles dispersed therein; and the thickness change rate of the finishing tape Et=(t1-t0) / t0 is 0.10-0.60.
[0014] In some embodiments, 0.35≤Kp≤1.15, 0.35≤Km≤1.20.
[0015] In some embodiments, the lithium-ion cell is cylindrical with a nominal diameter of 21±0.5 mm, a nominal height of 70±0.3 mm, and a 0.2C discharge capacity of 4.9 Ah to 5.2 Ah; and Lt is 35 mm to 120 mm, t0 is 0.025 mm to 0.100 mm, t1 is 0.030 mm to 0.130 mm, and Gr is 0.04 mm to 0.22 mm; and / or, The shortest coverage distance Sm from the end of the metal finishing layer to the corresponding outer edge of the finishing tape is 0.5 mm to 6.0 mm; the shortest insulation clearance distance St from the carbon filler-rich area in the finishing tape to the edge of the nearest active material layer on the electrode is 0.5 mm to 6.0 mm; the volume resistivity is less than 1.0 × 10⁻⁶ mm. 6 When the value is Ω·cm, both Sm and St are greater than or equal to 1.0 mm.
[0016] In some embodiments, after the lithium-ion cell is dropped once from a height of 1.5m in six directions at 100% SOC and 25±2℃, the axial displacement ΔZa of the core relative to the housing is less than or equal to 0.30mm, and the radial loosening ΔRr of the finishing layer is less than or equal to 0.15mm; or, After the lithium-ion battery cell is subjected to a sweep frequency vibration of 10Hz-55Hz for 2 hours on each of the three axes at 50% SOC and 25±2℃, the peeling rate of the finishing tape is less than or equal to 10%.
[0017] In some embodiments, the positive electrode comprises a layered high-nickel lithium transition metal oxide with a nickel content of 88 mol%-93 mol%; the negative electrode comprises artificial graphite and silicon carbide materials; and / or, the separator is a polyolefin separator coated with boehmite ceramic on one side.
[0018] In some embodiments, the housing is further provided with an electrolyte for wetting the winding core; the electrolyte includes 1.0 mol / L-1.2 mol / L of LiPF6 and a carbonate mixed solvent.
[0019] In some embodiments, an electrical device includes a lithium-ion battery cell as described above.
[0020] The lithium-ion battery cell and electrical device provided in the embodiments of the present invention can achieve the following technical effects: This invention sets a finishing tape and a metal finishing layer in the finishing area of the outer ring of the core, and defines the radial allowance Gr, the thickness t1 of the treated tape, the finishing pretension coefficient Kp, and the metal finishing space coefficient Km, so as to establish a measurable coupling relationship between the finishing structure and the inner diameter of the shell, the outer diameter of the core, and the change value, thereby improving the quality of the battery cell.
[0021] The above general description and the description below are exemplary and explanatory only, and are not intended to limit the invention. Attached Figure Description
[0022] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. The drawings described below are merely exemplary, and those skilled in the art can derive other embodiments based on the provided drawings without creative effort.
[0023] Figure 1 This is a schematic diagram of the radial cross-sectional structure of a 21700 lithium-ion battery cell according to an embodiment of the present invention; Figure 2 This is an embodiment of the present invention. Figure 1 A magnified schematic diagram of the local structure; Figure 3 This is a schematic diagram of the core unfolded state according to an embodiment of the present invention.
[0024] The reference numerals in the attached figures are as follows: 1. Shell; 2. Core; 3. Metal finishing layer; 4. Finishing tape; 41. Carbonaceous filler enrichment area; 5. Expanding adhesive layer; 6. Insulation layer; 7. Radial allowance. Detailed Implementation
[0025] To provide a more detailed understanding of the features and technical content of the embodiments of the present invention, the implementation of the present invention will be described in detail below with reference to specific embodiments. These embodiments are for illustrative purposes only and are not intended to limit the present invention. In the following technical description, for ease of explanation, several details are used to provide a full understanding of the disclosed embodiments. However, one or more embodiments may still be implemented without these details.
[0026] In this embodiment of the invention, the terms "comprising" and "having," and any variations thereof, are intended to cover non-exclusive inclusion.
[0027] Unless otherwise stated, the terms “multiple” or “multi-multiple” mean two or more.
[0028] It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of the present invention can be combined with each other.
[0029] like Figure 1 and Figure 2 As shown, this embodiment of the invention provides a lithium-ion battery cell, including a housing 1 and a core 2 coaxially arranged, wherein the core 2 is disposed within the housing 1; the core 2 is formed by sequentially stacking and winding a positive electrode sheet, a separator, and a negative electrode sheet. The core 2 also includes a finishing layer on at least part of its outer peripheral wall. Before impregnation, the finishing layer forms a radial allowance (Gr) 7 between its outer wall and the inner wall of the housing 1. The inner diameter of the housing 1 is Di. The maximum outer diameter of the core 2 in the area where the finishing layer is located is Dj, and Gr = (Di - Dj) / 2. The finishing layer includes a metal finishing layer 3 and a finishing tape 4. The metal finishing layer 3 is closely attached to the outer wall of the core 2, and the finishing tape 4 covers at least one end of the metal finishing layer 3. The length of the finishing tape 4 along the winding direction is Lt, and the thickness before covering is t0. The thickness of the finishing tape 4 after being immersed in a 25°C reference electrolyte for 24 hours, then heat-treated at 80°C for 30 minutes, and cooled to 25°C is t1. The thickness of the metal finishing layer 3 is tm, and the length covered along the winding direction is Lm. The units of Lt, t0, t1, Lm, and tm are all mm. It satisfies: Kp=[Lt / (π×Dj)]×(t1 / Gr), and 0.25≤Kp≤1.30; Km=(Lm / Lt)×[(t1+tm) / Gr], and 0.20≤Km≤1.40.
[0030] In this embodiment of the invention, the finishing layers on the outer ring of the core 2 are a finishing tape 4 and a metal finishing layer 3, and the radial allowance 7, the processed tape thickness t1, the finishing pretension coefficient Kp, and the metal finishing space coefficient Km are defined. In particular, Kp and Km are limited to specific ranges, where Kp is equivalent to the circumferential coverage ratio of the tape and the pretension capability formed by the processed thickness relative to the radial allowance; while Km is equivalent to the metal coverage ratio and the space occupied by the total thickness of the tape and metal layer relative to the radial allowance.
[0031] The radial allowance 7 is only used to represent the assembly space when the finishing tape 4 in the finishing layer is not wetted, and does not represent the working state of the finishing layer after being wetted by electrolyte or heated, and it always remains separated from the inner wall of the shell 1.
[0032] Kp combines the circumferential coverage ratio of the finishing tape 4, the standard processed thickness, and the radial allowance inside the shell to avoid spatial mismatch caused by simply increasing the thickness or coverage length of the finishing tape 4.
[0033] Km links the coverage ratio of the metal finishing layer 3 with the total thickness of the outer ring, so that the thin support and heat diffusion effect of the copper foil finishing layer are matched with the allowance for insertion into the shell.
[0034] In some embodiments, the finishing tape 4 includes a substrate layer and an adhesive layer adhered to the substrate layer, wherein carbonaceous filler is dispersed on the substrate layer and / or the adhesive layer; the carbonaceous filler accounts for 2 wt% to 20 wt% of the mass percentage of the finishing tape; and the thickness-direction volume resistivity of the finishing tape 4 at 25°C is 1.0 × 10⁻⁶. 4 Ω·cm-1.0×10 10 Ω·cm, in-plane thermal conductivity is 0.30W / (m·K)-3.00W / (m·K).
[0035] The substrate layer provides the finishing tape 4 with primary strength, electrolyte resistance, and dimensional stability, ensuring continuous coverage of the finishing tape around the core. The adhesive layer, through bonding with the metal finishing layer, outer electrode plate, or adjacent insulating surfaces, disperses the winding rebound force into in-plane shear loads. Carbonaceous filler is dispersed in the substrate layer and / or adhesive layer, forming a discontinuous in-plane thermal diffusion path. Controlling the carbonaceous filler content within the aforementioned range achieves a balance between thermal diffusion, insulation performance, and adhesive integrity, avoiding the risk of decreased volume resistivity or edge creepage caused by excessive filler.
[0036] In some embodiments, the substrate layer is made of one or more combinations of polyimide, polyethylene terephthalate, polypropylene, polyethylene, aramid paper, and polyamide-imide; the adhesive layer is made of one or more combinations of acrylate pressure-sensitive adhesive, silicone rubber pressure-sensitive adhesive, polyurethane adhesive, and epoxy modified adhesive; and the carbonaceous filler is made of one or more combinations of carbon black, conductive carbon black, graphite, graphene, carbon nanotubes, carbon fiber, and acetylene black.
[0037] The specific selection of components in the finishing tape 4 provided in this embodiment of the invention includes the following: the substrate layer is made of one or more combinations of polyimide, polyethylene terephthalate, polypropylene, polyethylene, aramid paper, and polyamide-imide; the adhesive layer is made of one or more combinations of acrylic pressure-sensitive adhesive, silicone rubber pressure-sensitive adhesive, polyurethane adhesive, and epoxy modified adhesive; and the carbonaceous filler is made of one or more combinations of carbon black, conductive carbon black, graphite, graphene, carbon nanotubes, carbon fiber, and acetylene black.
[0038] In some embodiments, the core 2 further includes an expanding adhesive layer 5 and an insulating layer 6 sequentially covering the outer ring of the finishing layer; the expanding adhesive layer 5 includes an acrylic pressure-sensitive adhesive matrix, and one or more combinations of liquid-absorbing expanding polymer particles, thermally expanding particles, porous elastomer particles and foaming polymer particles dispersed therein; and the thickness change rate Et=(t1-t0) / t0 of the expanding adhesive layer 5 is 0.10-0.60.
[0039] The expanded adhesive layer 5 undergoes a controlled thickness change after being immersed in electrolyte or heat-treated, which is used to compensate for the radial margin in the finishing area and buffer impact shear; the insulating layer 6 is located outside the expanded adhesive layer 5, which is used to isolate the carbon-containing filler area, the metal finishing layer and the shell or opposite polarity components, extend the creepage path and reduce the risk of leakage current under assembly extrusion and electrolyte residue conditions.
[0040] The insulating layer 6 is disposed between the expanding adhesive layer 5 and the inner wall of the housing. Based on its own ability to block electron flow, the insulating layer 6 can prevent short circuits between the core and the housing, thus improving the product's service life. The insulating layer 6 includes one or more of polyimide, polyethylene terephthalate, polypropylene, polyethylene, or aramid paper.
[0041] In some embodiments, 0.35≤Kp≤1.15, 0.35≤Km≤1.20.
[0042] This invention provides further preferred ranges for Kp and Km, linking the circumferential coverage ratio of the tape, the standard processed thickness, and the radial allowance within the shell to avoid spatial mismatch caused by simply increasing the tape thickness or coverage length. The coverage ratio of the metal finishing layer is linked to the total thickness of the outer ring, ensuring that the thin support and heat diffusion effect of the copper foil finishing layer matches the allowance within the shell.
[0043] The expanding adhesive layer 5 and the finishing tape can form a controlled fit or slight pretension within the space defined by Kp and Km, while avoiding continuous rigid interference.
[0044] In some embodiments, the lithium-ion cell is cylindrical with a nominal diameter of 21 mm, a nominal height of 70 mm, and a 0.2C discharge capacity of 4.9 Ah-5.2 Ah; and Lt is 35 mm-120 mm, t0 is 0.025 mm-0.100 mm, t1 is 0.030 mm-0.130 mm, and Gr is 0.04 mm-0.22 mm; and / or, The shortest coverage distance Sm from the end of the metal finishing layer 3 to the corresponding outer edge of the finishing tape 4 is 0.5mm to 6.0mm; the shortest insulation clearance distance St from the carbon filler enrichment area 41 in the finishing tape 4 to the edge of the nearest active material layer on the electrode is 0.5mm to 6.0mm; the volume resistivity is less than 1.0×10⁻⁶. 6 When the value is Ω·cm, both Sm and St are greater than or equal to 1.0 mm.
[0045] like Figure 3 As shown, the metal finishing layer 3 is the current collector of the electrode in the core 2, and the current collector is coated with active material; the shortest coverage distance from the end of the metal finishing layer 3 to the corresponding outer edge of the finishing tape 4 is Sm; the carbon filler enrichment area 41 on the finishing tape 4 is identified by SEM / EDS carbon element surface scan of the tape cross section, and the area with higher carbon signal in the adjacent substrate is used as the judgment object; the shortest insulation clearance distance from the carbon filler enrichment area 41 on the finishing tape 4 to the edge of the active material layer on the nearest electrode, the nearest electrode is usually the negative electrode.
[0046] The embodiments of the present invention provide the above-mentioned technical features for use in a specific cylindrical lithium-ion battery cell, wherein the cylindrical structure has a nominal diameter of 21mm and a nominal height of 70mm, and more specifically, a diameter of 20mm-22mm and a height of 65mm-72mm.
[0047] The cylindrical lithium-ion cell has a discharge capacity of 4.9Ah-5.2Ah at 0.2C. The parameters of this cylindrical lithium-ion cell are also limited to specific ranges, including Lt of 35mm-120mm, t0 of 0.025mm-0.100mm, t1 of 0.030mm-0.130mm, and Gr of 0.04mm-0.22mm.
[0048] In some embodiments, after the lithium-ion cell is dropped once from a height of 1.5m in six directions at 100% SOC and 25±2℃, the axial displacement ΔZa of the core relative to the housing is less than or equal to 0.30mm, and the radial loosening ΔRr of the finishing layer is less than or equal to 0.15mm; or, After the lithium-ion battery cell is subjected to a sweep frequency vibration of 10Hz-55Hz for 2 hours on each of the three axes at 50% SOC and 25±2℃, the peeling rate of the composite finishing tape is less than or equal to 10%.
[0049] This invention provides additional characteristics of the cylindrical lithium-ion battery cell, including that after the lithium-ion battery cell is dropped once from a height of 1.5m in six directions at 100% SOC and 25±2℃, the axial displacement ΔZa of the core relative to the casing is less than or equal to 0.30mm, and the radial loosening ΔRr of the finishing layer is less than or equal to 0.15mm; or, After the lithium-ion battery cell is subjected to a sweep frequency vibration of 10Hz-55Hz for 2 hours on each of the three axes at 50% SOC and 25±2℃, the peeling rate of the finishing tape is less than or equal to 10%.
[0050] In some embodiments, the positive electrode comprises a layered high-nickel lithium transition metal oxide with a nickel content of 88 mol%-93 mol%; the negative electrode comprises artificial graphite and silicon carbide materials; and / or, the separator is a polyolefin separator coated with boehmite ceramic on one side.
[0051] The combination of the above-mentioned positive electrode, negative electrode, and separator matches the peripheral finishing structure of this invention: the high-nickel positive electrode and the negative electrode composed of artificial graphite and silicon carbon materials can form a high areal capacity core, and the outer ring springback and finishing area space control after winding are more sensitive; the single-sided boehmite ceramic coated separator has heat resistance, puncture resistance, and electrolyte wetting properties, which is beneficial to maintaining the insulation isolation between the positive and negative electrodes in the finishing area. Therefore, the synergistic constraint of the finishing tape, the metal finishing layer, and the radial allowance can be used to control the outer ring loosening and edge electrical safety risks of this type of core.
[0052] The embodiments of the present invention provide specific definitions for each component in the core, such as the positive electrode sheet comprising a layered high-nickel lithium transition metal oxide with a nickel content of 88mol%-93mol%; the negative electrode sheet comprising artificial graphite and silicon carbide materials; and / or, the separator being a polyolefin separator coated with boehmite ceramic on one side.
[0053] In some embodiments, the housing is further provided with an electrolyte for wetting the winding core; the electrolyte includes 1.0 mol / L-1.2 mol / L of LiPF6 and a carbonate mixed solvent.
[0054] The LiPF6 and carbonate mixed solvent in the electrolyte provides the ion conduction and wetting environment required for core impregnation; cyclic carbonates help form an interfacial film, while linear carbonates help reduce system viscosity and improve impregnation. This electrolyte system also serves as a unified treatment benchmark for the thickness change rate Et of the finishing tape after impregnation and heat treatment, ensuring consistent testing conditions for the spatial variation of the finishing structure.
[0055] In some embodiments, an electrical device includes a lithium-ion battery cell as described above.
[0056] The lithium-ion battery cell provided by this invention can be used in electrical equipment, including handheld power tools such as hand drills, angle grinders, and electric shears. It has high energy density, stable performance, and improved safety.
[0057] Regarding the definition and measurement of some parameters of the lithium-ion battery cell in this invention: Di is the inner diameter of the casing at the height of the terminal region. Micro-focus X-ray CT scans were performed on the complete cell, and the inner wall of the casing was segmented on three circumferential sections avoiding weld seam and groove deformation. The inscribed circle was fitted to each section, and the average value of the three inner diameters was taken.
[0058] Dj is the maximum equivalent outer diameter of the core outline within the same height range. For the CT body data, take one layer every 0.5 mm axially, avoiding the end flattening area, and obtain the maximum outer diameter from the height covered by the finishing tape. Gr is calculated as (Di-Dj) / 2.
[0059] Lt represents the actual coverage length of the composite finishing tape along the winding direction. With the core unwound and the tape stretched, the circumferential unfolded length from the start to the end of the tape is measured using a 0.01mm resolution image measuring instrument. Wt represents the tape width perpendicular to the winding direction.
[0060] t0 is the thickness of the witness tape in the same batch before contact with the electrolyte; t1 is the thickness of the tape after being immersed in a 25℃ reference electrolyte for 24 hours, heat-treated at 80℃ for 30 minutes, and cooled at 25℃ for 30 minutes. Five points were measured for each sample and the average value was taken, Et=(t1-t0) / t0.
[0061] Lm and tm are the unfolded coverage length and cross-sectional thickness of the metal tail layer, respectively. Lm is measured using an image measuring instrument; tm is measured using an ion beam cross-section or a SEM after resin embedding and polishing, with at least five points taken at the head, middle and tail sections for averaging.
[0062] Vf represents the volume of the enclosed free space within the shell that is not occupied by the core, current collector, insulating components, and separable liquid phase. The internal space of the shell is three-dimensionally segmented using CT voxel calibration, and then the aforementioned solid volumes are subtracted. Electrolyte within micropores that cannot be distinguished by CT is not included in Vf.
[0063] Sm is the shortest coverage distance from the end of the metal finishing layer to the corresponding outer edge of the tape; St is the shortest insulation distance from the carbon filler area to the edge of the adjacent active material layer or the exposed metal edge. Both are measured using a calibration image after unfolding, and the minimum value is taken.
[0064] Example 1 Example 1 is the baseline preferred scheme, corresponding to the approximately 5Ah full-tab 21700 cell structure with black finishing tape and the outermost copper foil of the negative electrode.
[0065] Step 1: Preparation of positive electrode slurry. Based on the total mass of solid components, 97.25 wt% of layered high-nickel lithium transition metal oxide (Ni content approximately 90 mol%), 1.50 wt% of SP conductive carbon black, 0.10 wt% of SWCNT, and 1.15 wt% of PVDF were added to N-methylpyrrolidone. The mixture was first wetted at a low speed, then dispersed at a high speed and degassed under vacuum to achieve a solid content of 70 wt% and a viscosity of 5500 mPa·s.
[0066] Step 2: Preparation of the positive electrode sheet. The positive electrode slurry is coated on both sides of a 12μm aluminum foil, dried in three zones at 90℃, 110℃ and 130℃, rolled and cut to achieve a single-sided areal density of 12.70mg / cm², a total electrode sheet thickness of approximately 87μm, an estimated compaction density of approximately 3.48g / cm³, an effective electrode sheet length of approximately 1686mm, and a material zone width of approximately 60mm.
[0067] Step 3: Preparation of negative electrode slurry. Based on the total mass of solid components, 82.95 wt% artificial graphite, 13.50 wt% silicon carbide, 0.50 wt% SP, 0.25 wt% SWCNT, 1.10 wt% CMC and 1.70 wt% SBR were added to deionized water, dispersed and degassed to obtain the negative electrode slurry.
[0068] Step 4: Negative Electrode Preparation. The negative electrode slurry is coated on both sides of an 8.08 μm thick copper foil. After drying, rolling, and slitting, the areal densities of the two working surfaces are 5.48 mg / cm² and 5.45 mg / cm², respectively. The total thickness of the unthinned area of the electrode is approximately 86.7 μm, with an estimated compaction density of approximately 1.53 g / cm³. The effective length of the negative electrode is 1719 mm and 1661 mm on each side. A 62 mm copper foil extension is retained at the tail of the negative electrode as a metal finishing layer, tm = 0.00808 mm.
[0069] Step 5: Separator preparation. The separator is composed of a wet-process polyethylene base membrane and a single-sided boehmite layer. The base membrane thickness is about 7.8 μm, the ceramic layer thickness is about 2.45 μm, and the total thickness is about 10.25 μm. When winding, the ceramic side faces the negative electrode.
[0070] Step 6: Preparation of the finishing tape. A 25μm polyimide / polyester composite substrate is used, with a 20μm acrylic pressure-sensitive adhesive layer and a 10μm liquid-absorbing and swelling adhesive layer coated on one side. Based on the total solids mass of the tape, the adhesive layers contain 8wt% carbon black and flake graphite, and 3wt% insulating and thermally conductive boehmite. The tape is black, with a total thickness t0 = 0.055mm, width Wt = 6.0mm, and coverage arc length Lt = 64mm. After fixation, impregnation, and heat treatment, Et = 0.25, t1 = 0.06875mm; the in-plane thermal conductivity is 0.85W / (m·K), and the volume resistivity is 1.0×10⁻⁶. 6 Ω·cm, initial 180° peel strength is 8.0 N / 25 mm.
[0071] Step 7: Winding and Finishing. Wind the positive electrode sheet, separator, and negative electrode sheet into a cylindrical core, ensuring the outermost copper foil extension of the negative electrode forms a metal finishing layer, Lm = 62mm; attach black composite finishing tape to cover the ends of the metal finishing layer, Sm = 1.2mm, St = 1.5mm. Core height Hj = 66.1mm, maximum outer diameter of the finishing area Dj = 20.46mm. Inner diameter of the shell Di = 20.68mm, Gr = 0.11mm, Vf = 0.55cm³. Therefore, Kp = 0.622, Km = 0.676.
[0072] Step 8: Assembly. Using a cylindrical steel shell with a bottom thickness of approximately 0.40mm as structural anchor points, flatten the positive and negative end portions, and complete the welding, insertion into the shell, grooving, and sealing of the positive and negative current collector components. The end of the metal finishing layer must not directly contact the shell or the current collector component of the opposite polarity.
[0073] Step 9: Liquid injection, formation, and capacity testing. A 1.1 mol / L LiPF6 mixed solvent with an EC / EMC / DEC ratio of 3:5:2 was used, along with 1.0 wt% FEC, 0.5 wt% VC, and 1.0 wt% 1,3-propanesulfonyl lactone. After liquid injection, the cell was allowed to stand at 25°C for 24 hours. It was then charged at 0.05C to 3.0V, 0.1C to 3.8V, and 0.2C constant current / constant voltage to 4.2V with a cutoff current of 0.05C. The venting was completed, and the cell was resealed. After aging at 45°C for 48 hours, capacity testing was performed to obtain a cell with a capacity of approximately 5.0 Ah.
[0074] Example 2 The difference between this embodiment and Embodiment 1 is that the total coating thickness of the composite substrate layer and the adhesive layer is adjusted to 0.035mm, so that t0 changes from 0.055mm to 0.035mm, t1 changes from 0.06875mm to 0.04375mm, Kp changes from 0.622 to 0.396, and Km changes from 0.676 to 0.456; other conditions are the same as in Embodiment 1.
[0075] Example 3 The difference between this embodiment and Embodiment 1 is that the total coating thickness of the composite substrate layer and the adhesive layer is adjusted to 0.080 mm, so that t0 changes from 0.055 mm to 0.080 mm, t1 changes from 0.06875 mm to 0.100 mm, Kp changes from 0.622 to 0.905, and Km changes from 0.676 to 0.951; other conditions are the same as in Embodiment 1.
[0076] Example 4 The difference between this embodiment and Embodiment 1 is that the tape cutting width is adjusted to 4.5mm, so that Wt changes from 6.0mm to 4.5mm; other conditions are the same as in Embodiment 1.
[0077] Example 5 The difference between this embodiment and Embodiment 1 is that the tape cutting width is adjusted to 8.5mm, so that Wt changes from 6.0mm to 8.5mm; other conditions are the same as in Embodiment 1.
[0078] Example 6 The difference between this embodiment and Embodiment 1 is that by adjusting the start and end positions of the adhesive application to 45mm circumferential coverage, Lt changes from 64mm to 45mm, Kp changes from 0.622 to 0.437, and Km changes from 0.676 to 0.962; other conditions are the same as in Embodiment 1.
[0079] Example 7 The difference between this embodiment and Embodiment 1 is that by adjusting the start and end positions of the adhesive application to 95mm circumferential coverage, Lt changes from 64mm to 95mm, Kp changes from 0.622 to 0.923, and Km changes from 0.676 to 0.456; other conditions are the same as in Embodiment 1.
[0080] Example 8 The difference between this embodiment and Embodiment 1 is that by adjusting the amount of carbon black and flake graphite to 4 wt% of the total solid mass of the tape, the carbonaceous filler content changes from 8 wt% to 4 wt%, the in-plane thermal conductivity changes from 0.85 W / (m·K) to 0.45 W / (m·K), and the volume resistivity changes from 1.0 × 10⁻⁶. 6 Ω·cm becomes 5.0×10 7 Ω·cm; other conditions are the same as in Example 1.
[0081] Example 9 The difference between this embodiment and Embodiment 1 is that by adjusting the amount of carbon black and flake graphite to 15 wt% of the total solid mass of the tape, the carbonaceous filler content changes from 8 wt% to 15 wt%, the in-plane thermal conductivity changes from 0.85 W / (m·K) to 1.35 W / (m·K), and the volume resistivity changes from 1.0 × 10⁻⁶. 6 Ω·cm becomes 5.0×10 4 Ω·cm; other conditions are the same as in Example 1.
[0082] Example 10 The difference between this embodiment and Embodiment 1 is that by using a nickel-plated copper foil with a thickness of 0.006 mm for the finishing section, tm changes from 0.00808 mm to 0.006 mm and Km changes from 0.676 to 0.658; other conditions are the same as in Embodiment 1.
[0083] Example 11 The difference between this embodiment and Embodiment 1 is that the cutting length of the outermost copper foil extension section of the negative electrode is adjusted to 95mm, so that Lm changes from 62mm to 95mm and Km changes from 0.676 to 1.036; other conditions are the same as in Embodiment 1.
[0084] Example 12 The difference between this embodiment and Embodiment 1 is that the proportion of liquid-absorbing and swelling polymer particles in the swelling adhesive layer 5 is adjusted to 18wt%, so that Et changes from 0.25 to 0.45, t1 changes from 0.06875mm to 0.07975mm, Kp changes from 0.622 to 0.722, and Km changes from 0.676 to 0.773; other conditions are the same as in Embodiment 1.
[0085] Example 13 The difference between this embodiment and Embodiment 1 is that by using a cylindrical shell with an inner diameter Di of 20.58 mm, Gr changes from 0.11 mm to 0.06 mm, Kp changes from 0.622 to 1.140, and Km changes from 0.676 to 1.240; other conditions are the same as in Embodiment 1.
[0086] Example 14 The difference between this embodiment and Embodiment 1 is that by using a cylindrical shell with an inner diameter Di of 20.86 mm, Gr changes from 0.11 mm to 0.20 mm, Kp changes from 0.622 to 0.342, and Km changes from 0.676 to 0.372; other conditions are the same as in Embodiment 1.
[0087] Comparative Example 1 The difference between this comparative example and Example 1 is that by eliminating the liquid-absorbing and swelling particles and using a non-swelling acrylate adhesive layer, Et changes from 0.25 to 0.02, t1 changes from 0.06875mm to 0.05610mm, Kp changes from 0.622 to 0.508, and Km changes from 0.676 to 0.565; other conditions are the same as in Example 1.
[0088] Comparative Example 2 The difference between this comparative example and Example 1 is that the starting and ending positions of the adhesive application are adjusted to cover the entire circumference by 20mm, so that Lt changes from 64mm to 20mm, Kp changes from 0.622 to 0.194, and Km changes from 0.676 to 2.165; other conditions are the same as in Example 1.
[0089] Comparative Example 3 The difference between this comparative example and Example 1 is that by adjusting the amount of carbon filler to 0 wt% and using transparent polyester tape, the carbon filler content changes from 8 wt% to 0 wt%, the in-plane thermal conductivity changes from 0.85 W / (m·K) to 0.20 W / (m·K), and the volume resistivity changes from 1.0 × 10⁻⁶. 6 Ω·cm becomes 1.0×10 12 Ω·cm; other conditions are the same as in Example 1.
[0090] Comparative Example 4 The difference between this comparative example and Example 1 is that by adjusting the amount of carbon black added to 30 wt% of the total solid mass of the tape, the carbonaceous filler content changes from 8 wt% to 30 wt%, and the volume resistivity changes from 1.0 × 10⁻⁶. 6 The Ω·cm becomes 8.0×10 2 Ω·cm; other conditions are the same as in Example 1.
[0091] Comparative Example 5 The difference between this comparative example and Example 1 is that the outermost copper foil extension section of the negative electrode is removed, so that Lm changes from 62mm to 0mm, tm changes from 0.00808mm to 0mm, and Km changes from 0.676 to 0; other conditions are the same as in Example 1.
[0092] Comparative Example 6 The difference between this comparative example and Example 1 is that the cutting length of the outermost copper foil extension of the negative electrode is adjusted to 140mm, so that Lm changes from 62mm to 140mm, Km changes from 0.676 to 1.528, and the end coverage distance Sm of the metal layer changes from 1.2mm to 0.2mm; other conditions are the same as in Example 1.
[0093] Comparative Example 7 The difference between this comparative example and Example 1 is that the composite finishing tape is offset 1.3 mm axially towards the edge of the active material layer, so that St changes from 1.5 mm to 0.2 mm; other conditions are the same as in Example 1.
[0094] Comparative Example 8 The difference between this comparative example and Example 1 is that the proportion of thermally expanded microspheres in the expanded adhesive layer 5 is adjusted to 35wt%, so that Et changes from 0.25 to 0.95, t1 changes from 0.06875mm to 0.10725mm, Kp changes from 0.622 to 0.971, and Km changes from 0.676 to 1.015; other conditions are the same as in Example 1.
[0095] Comparative Example 9 The difference between this comparative example and Example 1 is that by using a cylindrical shell with an inner diameter Di of 20.49 mm, Gr changes from 0.11 mm to 0.015 mm, Kp changes from 0.622 to 4.564, and Km changes from 0.676 to 4.962; other conditions are the same as in Example 1.
[0096] Performance tests were conducted on the above-described embodiments and comparative products. Except for the tape material test, three independent cells were prepared for each example or comparative example for each destructive test, i.e., n=3; the same cell was not used consecutively for two destructive safety tests. All equipment underwent metrological calibration before testing, and raw data, including CT body data, time-voltage-current-temperature data, images, and failure photographs, were saved according to sample number. The following judgment thresholds are used to compare the boundaries of the examples and do not represent a replacement for applicable mandatory product safety standards.
[0097] 1. CT testing of internal radial allowance, core outer diameter, and free volume. Sample preparation: Take three intact battery cells that have been calibrated and allowed to stand for 7 days, adjust them to 30% SOC (charged to 30% SOC using a constant current and constant voltage at 0.2C), and allow them to stand at 25±2℃ for 2 hours. The equipment used is a microfocus X-ray CT with a voxel size no larger than 20μm, a tube voltage of 160kV, a tube current of 100μA, and a rotation step no greater than 0.25°. The scanning range covers the entire housing, focusing on reconstructing the axial height range of the tape finishing the process.
[0098] Test location and procedure: Using the shell axis as the Z-axis, establish three cross-sections at the midpoint of the tape width and 2mm above and below it; divide the inner wall of the shell and the outer contour of the core, and fit Di and Dj respectively. Calculate the radial margin of each cross-section using Gr=(Di-Dj) / 2, and use the minimum Gr among the three cross-sections as the judgment value. Use the same threshold to perform three-dimensional segmentation of the gas phase or unoccupied space inside the shell, and calculate Vf. Record Di, Dj, Gr of the three cross-sections and the overall Vf for each cell, and report the average, standard deviation, and minimum value of the three cells. The judgment criterion is that there is no negative gap or obvious shell indentation with a continuous length exceeding 10mm in the tape width at the end.
[0099] 2. Axial and radial displacement test of the core after drop test Sample preparation: Take 3 complete battery cells, charge them at a constant current and constant voltage of 0.5C to 4.20V, cutoff current of 0.05C, and after reaching 100% SOC, let them stand at 25±2℃ for 2 hours. Before testing, perform CT scans as per Test 1. The axial reference distance Za is the shortest distance from the outer edge of the positive end of the core to the fitted plane of the lower edge of the groove; the radial reference gap Rr is 12 local gaps measured every 30° in the finishing area.
[0100] Equipment, location, and procedures: A 1.5m drop platform with a guide release mechanism was used to drop the battery cell onto a 20mm thick flat steel plate. The cell was dropped once each along the positive terminal, negative terminal, and four mutually orthogonal radial directions, with 5-minute intervals between each drop; the ambient temperature was 25±2℃. After each drop, the cell was left to stand for 30 minutes and then re-CT scanned at the same coordinates. ΔZa = |Za,after-Za,before|; ΔRr is the maximum absolute value of the local gap change before and after the drop at 12 locations. Shell deformation, open-circuit voltage change, leakage, fire, and explosion were recorded. The judgment criteria were ΔZa ≤ 0.30mm, ΔRr ≤ 0.15mm, and no fire, explosion, or leakage.
[0101] 3. Vibration test for loosening of the outer ring and peeling of the tape. Sample preparation: Take 3 intact battery cells, adjust to 50% SOC, and let stand at 25±2℃ for 2 hours. Record the initial open circuit voltage, ACR, and CT final images. The equipment uses an electric vibration table, and the battery cells are fixed with rigid clamps but no axial preload is applied to the housing.
[0102] Procedure: A continuous frequency sweep of 1 oct / min was performed between 10Hz and 55Hz, with a full displacement of 0.8mm. Vibration was performed for 2 hours each along the cell's axial direction and two mutually perpendicular radial directions. After vibration, the cell was allowed to stand for 30 minutes, and the open-circuit voltage, ACR, and CT were remeasured. The cell was then discharged to 2.5V and disassembled and unwound in an Ar glove box where both water and oxygen levels were below 1ppm. The cumulative length Lb of the separation between the tape and the original adhesive area was measured and calculated using the peel rate Rb = Lb / Lt × 100%. A full-view and partial microscopic image of each cell was preserved. The criteria for judgment were: Rb ≤ 10%, no lifting or tearing of the tape at the metal end layer, and ACR increment ≤ 0.20mΩ.
[0103] 4. Tests on tape expansion rate and adhesion retention rate after thermal shock. Sample preparation: Cut six 100mm × 25mm strips from each batch of the same witness tape. Thickness was measured on three of them, and 180° peeling was performed on the other three. The material samples were free of SOC. The initial thickness t0 was measured at five points along the length using a thickness gauge with a contact pressure of 20kPa. The initial peel strength F0 was measured at 100mm / min from the SUS304 plate, and the average force of the middle 50mm stable zone was taken.
[0104] Procedure: Immerse the sample completely in the reference electrolyte of Example 1 and maintain at 25±1℃ for 24 hours; after removal, gently touch with lint-free paper to remove surface free liquid, place in an oven at 80±1℃ without tension for 30 minutes, and then cool at 25±1℃ for 30 minutes. Measure t1 at the same location and test the peel strength F1 after treatment. Et=(t1-t0) / t0; Adhesion retention rate Rf=F1 / F0×100%. Record the thickness at five points, peel force curve, average value, and standard deviation for each sample. The judgment criteria are: Et falls within the corresponding design range, Rf≥70%, and the sample has no delamination, powdering, or continuous bubbles.
[0105] 5. Tape volume resistivity test Three 20mm diameter discs were cut from each batch of witness tape and conditioned for 24 hours at 23±2℃ and 50±5% relative humidity. A high-resistivity meter with a protective ring electrode (effective electrode area A=3.14cm²) was used. After applying a 500V DC voltage for 60 seconds, the stable resistance R was read. The volume resistivity was calculated using ρv=R×A / t0, converted to cm based on the untreated t0 obtained from test 4. If R was below the high-resistivity meter's range, the surface resistivity was measured using a four-probe meter and converted in conjunction with the thickness, and the method switch was noted in the report. Each disc was tested three times, and the geometric mean of each disc was taken. The geometric mean of the three discs was then reported. The criterion for judgment was that the ratio of the maximum to the minimum value of ρv in the same group did not exceed 10.
[0106] 6. Tape thermal conductivity test Three 30mm × 30mm laminated samples were prepared from each batch of witness tape. Each sample was laminated to a total thickness of 1.0mm to 2.0mm, and visible air gaps were excluded. A transient planar thermal pyrometer was used to measure the in-plane and thickness thermal conductivity at 25±1℃ and a clamping pressure of 0.08MPa. A blank substrate with the same number of layers was used for interfacial thermal resistance correction. Each sample was repeated three times, and the original temperature rise-time curve and fitting residual were recorded. The average of nine valid results was taken. The judgment criteria were: in-plane thermal conductivity within the design range, single fitting residual ≤3%, and intra-group relative standard deviation ≤10%.
[0107] 7. External Short Circuit Auxiliary Safety Test Three fully charged (100% SOC) battery cells were placed at 25±2℃ for 2 hours. An external short-circuit device with a DC internal resistance of 10±1mΩ was used to connect the positive and negative terminals. A type K thermocouple was placed at the midpoint of the casing axis, 10mm below the positive terminal, and 10mm above the negative terminal, with a sampling frequency of 10Hz. The circuit was closed and maintained for 60 minutes, or until the peak temperature was reached and then decreased by 10℃ for at least 10 minutes. Current, terminal voltage, temperatures at the three measuring points, venting, leakage, ignition, and explosion were recorded. The judgment criteria were no ignition and no explosion; the highest temperature and venting status were used for inter-group comparison data.
[0108] 8. Extrusion-assisted safety test Three 100% SOC (State of Charge) intact battery cells were taken and placed at 25±2℃ for 2 hours. The cell axis was placed horizontally, and a 32mm diameter cylindrical indenter was used to apply radial load at 5mm / s, with the center of the indenter aligned with the midpoint of the axial width of the tape. The termination condition was fixed as the first of the following: load reaching 13kN, radial deformation of the casing reaching 50% of the initial diameter, or voltage drop reaching 1 / 3 of the initial voltage. After termination, the load was maintained for 10 minutes and observed for 60 minutes. Force-displacement, voltage, temperature at the midpoint of the casing, and failure images were recorded. The judgment criteria were no fire and no explosion; if tape penetration, metal edge contact marks, abnormal smoke, or continuous leakage occurred, it was recorded as structural failure.
[0109] 9. ACR, DCR and 40A temperature rise auxiliary tests ACR Test: Each group of 3 cells was adjusted to 30% SOC at 25±1℃ and allowed to stand for 2 hours. The cells were then tested 3 times using a 1kHz AC internal resistance meter, and the arithmetic mean was taken. DCR Test: Another 3 cells were charged to 100% SOC and allowed to stand for 2 hours. They were then discharged at 40A for 10 seconds. DCR was calculated as (U0-U10s) / 40A, where U0 is the voltage before the pulse and U10s is the voltage at the end of the 10 seconds. 40A Temperature Rise Test: 3 cells from the same batch were fully charged to standard capacity and discharged at 40A to 2.5V at 25±1℃ in an environment without active airflow. Thermocouples were placed at 1 / 2 of the casing height, circumferentially avoiding the weld seam by at least 30°. The sampling frequency was 1Hz, and the highest temperature Tmax within 300 seconds from the start to the end of the discharge was recorded. The average and standard deviation of all three data points were reported as supplementary information for the final structural design.
[0110] The structural and performance data for all embodiments and comparative examples are shown in Tables 1 and 2 below: Table 1
[0111] Table 2
[0112] The following is a summary of Tables 1 and 2 above: 1. Total thickness of tape As shown in Examples 1 to 3, when t0 increases from 0.035 mm to 0.080 mm, the thickness of the treated tape and Kp increase accordingly, while ΔZa decreases from 0.24 mm to 0.15 mm. This indicates that a thicker substrate and adhesive layer can more fully adhere to the step formed by the copper foil tail and improve the outer ring constraint. When the thickness is too low, the effective cross-sectional area of the tape to withstand impact shear and the energy storage of compression rebound are insufficient, and the drop load is more easily converted into interlayer slippage of the outer ring. Increasing the thickness can improve buffering and bonding stability. However, when t0 continues to increase or is used under a smaller Gr, t1+tm will occupy too much radial space, causing Km to increase, and the friction of the housing, local compaction of the outer ring, and metal edge stress will increase accordingly. Therefore, the thickness cannot be relaxed independently of Gr and the thickness of the metal layer superposition. The common range of Kp and Km gives the boundary for anti-loosening and assemblability.
[0113] 2. Tape width As shown in Examples 1, 4, and 5, when Wt increases from 4.5 mm to 8.5 mm, Kp and Km remain unchanged, while ΔZa, ΔRr, and vibration peel rate continuously decrease, proving that the tape width mainly affects axial coverage and edge peeling path, rather than circumferential preload. If Wt is too small, the adhesive width obtained at the axial edge of the metal layer and the diaphragm termination area is insufficient, and shear stress is concentrated on the narrow edge during drop, making it easy for the peeling front to span the entire tape width. A moderate increase in Wt can disperse shear stress and increase the arrangement space for Sm and St. If Wt is too large and enters the flattened end or the edge of the active layer, it may cover the venting channel, approach exposed metal, or introduce end wrinkles. Therefore, a range of 3.0 mm to 12.0 mm balances outer ring fixation, end insulation, and avoidance of the flattened area of the full tab.
[0114] 3. Circumferential coverage length As shown in Examples 6, 1, 7, and Comparative Example 2, when Lt increases from 20mm to 95mm, the proportion of tape coverage around the perimeter increases, the probability of the uncovered outer ring acting as a relaxation starting point decreases, ΔZa decreases from 0.55mm to 0.13mm, and the vibration peel rate decreases from 26.0% to 3.0%. Too short Lt not only causes Kp to fall below the lower limit but also makes the predetermined Lm too large relative to Lt, increasing Km to 2.165, resulting in a coverage mismatch of "long metal layer, short tape". A moderate increase in Lt can expand the bonding area and disperse the winding rebound force; however, excessive coverage increases the probability of tape overlap and localized thick areas, and at a fixed Lm, it reduces Km, weakening the common finishing ratio of the metal layer and the tape. Therefore, using Lt / (πDj) and Lm / Lt as inputs to Kp and Km respectively can simultaneously limit insufficient coverage and ineffective excessive length.
[0115] 4. Carbonaceous filler content and electrothermal properties According to Examples 8, 1, and 9, and Comparative Examples 3 and 4, when the carbonaceous filler content increases from 0 to 15 wt%, the in-plane thermal conductivity increases from 0.20 W / (m·K) to 1.35 W / (m·K), indicating that discrete carbon black and flake graphite can form a thermal diffusion path within the tape surface. When the filler content is insufficient, although the tape has high insulation, localized heat on the outer ring is difficult to homogenize circumferentially; with a moderate filler content, both thermal diffusion and insulation can be achieved. When the filler content reaches 30 wt%, a continuous conductive network is formed in the particle contact, and the volume resistivity decreases to 8.0 × 10⁻⁶. ² Ω·cm, when combined with a smaller St, makes leakage current or compression short circuits more likely. Therefore, the filler content must be limited together with ρv, thermal conductivity, and insulation clearance distance, and "the higher the thermal conductivity, the better" cannot replace electrical safety boundaries.
[0116] 5. Thickness and coverage length of the metal finishing layer As shown in Examples 1, 10, 11, and Comparative Examples 5 and 6, the metal tail layer provides thin outer ring support and circumferential thermal continuity. After removing the metal layer, Km becomes 0, and the roll tail mainly relies on the tape to withstand the winding springback; ΔRr and vibration peeling rate increase to 0.18 mm and 12.0%, respectively. When tm is reduced from 0.00808 mm to 0.006 mm, the space occupied decreases, but the support and heat diffusion are slightly weakened. Increasing Lm to 95 mm can still maintain stability through tape coverage, but increasing it to 140 mm causes Km to exceed the upper limit and Sm to shrink, resulting in contact marks on the metal end after extrusion. A metal layer that is too thin or too short is insufficient to provide effective support, while one that is too thick or too long occupies Gr and increases the risk of exposed edges. Therefore, tm, Lm, t1, and Gr need to be constrained together by Km.
[0117] 6. Expansion rate According to Examples 1 and 12, and Comparative Examples 1 and 8, when Et increases from 0.02 to 0.45, the tape can compensate for the micro-gaps formed after liquid injection, thermal cycling, and mechanical impact. ΔZa decreases from 0.42 mm to 0.12 mm, indicating that moderate liquid absorption expansion or thermal response rebound can establish flexible radial preload. When Et is too low, the fixing effect mainly relies on the initial pressure-sensitive adhesive, and the softening of the adhesive layer caused by electrolyte wetting will reduce the long-term shear resistance. When Et is moderate, t1 increases while still retaining compression margin, which can absorb impact energy. When Et reaches 0.95, although the displacement data is low, the peel retention rate drops to 55%. Excessive expansion causes cohesive failure of the adhesive layer, edge lifting, and local extrusion of the outer ring. Therefore, Et needs to be matched with Gr, t0, and the thickness of the metal layer, and the peel retention rate should be used to exclude schemes that rely solely on excessive expansion to obtain low displacement.
[0118] 7. Inner radial allowance and free volume As shown in Examples 13, 1, 14, and Comparative Example 9, when Gr decreases from 0.20 mm to 0.06 mm, the ratio of tape thickness to gap increases, Kp and Km increase, and drop displacement decreases. However, when Gr continues to decrease to 0.015 mm, both Kp and Km exceed 4.5. Even with a small static displacement, this results in excessively high assembly prestress, which can easily lead to stress concentration in the shell, compression of electrode pores, and puncture of metal ends during extrusion. Excessive Gr prevents the tape from continuously contacting or constraining the inner wall of the shell after expansion, resulting in a longer acceleration stroke for the outer ring during drop. Vf also affects gas generation buffering and pressure distribution. Therefore, a smaller Gr is not always better. A feasible window of 0.04 mm to 0.22 mm, along with upper limits for Kp and Km, is used to balance anti-loosening, manufacturability of the casing, and safety buffering.
[0119] 8. Edge insulation setback distance As shown in Examples 1, 9, 6, and 7, Sm and St do not directly change Kp or Km, but they determine whether the carbon-containing tape and the metal termination layer can be used safely. When Sm is too small, the metal end can penetrate the tape edge and approach the housing or polarity component after the adhesive layer softens, is sheared from a drop, or is deformed by compression. When St is too small, the creepage path between the filler-rich area and the edge of the active material layer or exposed metal is shortened, making leakage current more likely, especially under electrolyte residue conditions. When Sm and St are too large, the effective bonding area is compressed, reducing the utilization rate of the metal layer coverage. Therefore, this invention sets the values in the range of 0.5 mm to 6.0 mm, and raises the lower limit to 1.0 mm when ρv is below 1.0 × 10^6 Ω·cm, maintaining a verifiable balance between thermal diffusion benefits and short-circuit risk.
[0120] The carbonaceous filler enrichment region refers to the area on the cross-section of the finishing tape that exhibits a high carbon element signal intensity relative to the adjacent substrate layer or adhesive layer matrix, identified by scanning electron microscopy and energy-dispersive X-ray spectroscopy. Sm is the shortest distance from the end of the metal finishing layer to the corresponding outer edge of the finishing tape, and St is the shortest distance from this enrichment region to the edge of the adjacent active material layer or the exposed metal edge. The measurement locations of Sm and St are shown in [reference needed]. Figure 2 .
[0121] The technical effects brought about by this invention include: 1. Kp combines the circumferential coverage ratio of the tape, the standard processed thickness, and the radial allowance inside the shell to avoid spatial mismatch caused by simply increasing the tape thickness or coverage length.
[0122] 2. Km links the coverage ratio of the metal finishing layer with the total thickness of the outer ring, so that the thin support and heat diffusion effect of the copper foil finishing layer are matched with the allowance for insertion into the shell.
[0123] 3. By limiting the expansion adhesive layer 5 by Et and peel retention rate, it can maintain flexible pre-tightening after liquid injection and thermal cycling, while suppressing local compression caused by excessive expansion.
[0124] 4. By utilizing the combined boundaries of volume resistivity, thermal conductivity, Sm and St, fillers such as carbon black can improve thermal diffusion and reduce the risk of short circuits caused by metal ends or filler-rich areas.
[0125] The foregoing description fully illustrates embodiments of the invention to enable those skilled in the art to practice them. Other embodiments may include structural and other changes. The embodiments represent only possible variations. Individual components and functions are optional unless explicitly required, and the order of operation may vary. Some portions and features of some embodiments may be included in or replace portions and features of other embodiments. Embodiments of the invention are not limited to those already described above, and various modifications and changes can be made without departing from their scope. The scope of the invention is limited only by the appended claims.
Claims
1. A lithium-ion battery cell, comprising a housing and a core coaxially arranged, the core being disposed within the housing; the core is formed by sequentially stacking and winding a positive electrode sheet, a separator, and a negative electrode sheet, characterized in that, The core also includes a finishing layer on at least part of the outer peripheral wall; a radial allowance Gr is formed between the outer wall of the finishing layer and the inner wall of the shell, the inner diameter of the shell is Di, the maximum outer diameter of the core in the region where the finishing layer is located is Dj, and Gr=(Di-Dj) / 2; The finishing layer includes a metal finishing layer and a finishing tape. The metal finishing layer is in close contact with the outer wall of the core, and the finishing tape covers at least one end of the metal finishing layer. The length of the finishing tape along the winding direction is Lt, and the thickness before covering is t0. The thickness of the finishing tape after being immersed in a 25°C reference electrolyte for 24 hours, then heat-treated at 80°C for 30 minutes, and cooled to 25°C is t1. The thickness of the metal finishing layer is tm, and the length covered along the winding direction is Lm. The units of Lt, t0, t1, Lm, and tm are all mm. It satisfies: Kp=[Lt / (π×Dj)]×(t1 / Gr), and 0.25≤Kp≤1.30; Km=(Lm / Lt)×[(t1+tm) / Gr], and 0.20≤Km≤1.
40.
2. The lithium-ion battery cell according to claim 1, characterized in that, The finishing tape includes a substrate layer and an adhesive layer adhered to the substrate layer, wherein carbonaceous filler is dispersed on the substrate layer and / or the adhesive layer; the substrate layer is adhered to the metal finishing layer; the carbonaceous filler accounts for 2wt% to 20wt% of the mass percentage of the finishing tape; the thickness-direction volume resistivity of the finishing tape at 25°C is 1.0 × 10⁻⁶. 4 Ω·cm-1.0×10 10 Ω·cm, in-plane thermal conductivity is 0.30W / (m·K)-3.00W / (m·K).
3. The lithium-ion battery cell according to claim 2, characterized in that, The substrate layer is made of one or more combinations of polyimide, polyethylene terephthalate, polypropylene, polyethylene, aramid paper, and polyamide-imide; the adhesive layer is made of one or more combinations of acrylic pressure-sensitive adhesive, silicone rubber pressure-sensitive adhesive, polyurethane adhesive, and epoxy modified adhesive; and the carbonaceous filler is made of one or more combinations of carbon black, conductive carbon black, graphite, graphene, carbon nanotubes, carbon fiber, and acetylene black.
4. The lithium-ion battery cell according to claim 2 or 3, characterized in that, The finishing tape further includes an expanding adhesive layer and an insulating layer, wherein the expanding adhesive layer and the insulating layer are sequentially coated on the adhesive layer; the expanding adhesive layer includes an acrylic pressure-sensitive adhesive matrix, and one or more combinations of liquid-absorbing and expanding polymer particles, thermally expanding particles, porous elastomer particles and foamed polymer particles dispersed therein; and the thickness change rate of the finishing tape Et=(t1-t0) / t0 is 0.10-0.
60.
5. The lithium-ion battery cell according to claim 1, characterized in that, 0.35≤Kp≤1.15, 0.35≤Km≤1.
20.
6. The lithium-ion battery cell according to claim 4, characterized in that, The lithium-ion battery cell is cylindrical, with a nominal diameter of 21±0.5mm, a nominal height of 70±0.3mm, and a 0.2C discharge capacity of 4.9Ah to 5.2Ah; and Lt is 35mm-120mm, t0 is 0.025mm-0.100mm, t1 is 0.030mm-0.130mm, and Gr is 0.04mm-0.22mm; and / or, The shortest coverage distance Sm from the end of the metal finishing layer to the corresponding outer edge of the finishing tape is 0.5 mm to 6.0 mm; the shortest insulation clearance distance St from the carbon filler-rich area in the finishing tape to the edge of the nearest active material layer on the electrode is 0.5 mm to 6.0 mm; the volume resistivity is less than 1.0 × 10⁻⁶ mm. 6 When the value is Ω·cm, both Sm and St are greater than or equal to 1.0 mm.
7. The lithium-ion battery cell according to claim 6, characterized in that, After the lithium-ion battery cell is dropped once from a height of 1.5m in six directions at 100% SOC and 25±2℃, the axial displacement ΔZa of the core relative to the shell is less than or equal to 0.30mm, and the radial loosening ΔRr of the finishing layer is less than or equal to 0.15mm; or, After the lithium-ion battery cell is subjected to a sweep frequency vibration of 10Hz-55Hz for 2 hours on each of the three axes at 50% SOC and 25±2℃, the peeling rate of the finishing tape is less than or equal to 10%.
8. The lithium-ion battery cell according to claim 7, characterized in that, The positive electrode comprises a layered high-nickel lithium transition metal oxide with a nickel content of 88 mol%-93 mol%; the negative electrode comprises artificial graphite and silicon carbon materials; and / or, the separator is a polyolefin separator coated with boehmite ceramic on one side.
9. The lithium-ion battery cell according to claim 8, characterized in that, The housing is also provided with an electrolyte for wetting the winding core; the electrolyte includes 1.0 mol / L-1.2 mol / L of LiPF6 and a carbonate mixed solvent.
10. An electrical appliance, characterized in that, Including the lithium-ion battery cell as described in any one of claims 1-9.